Role of afferent and efferent renal nerves in the development of AngII‐salt hypertension in rats. Issue 3 (6th February 2018) - Foss, Jason D.; Fiege, Jessica; Shimizu, Yoji; Collister, John P.; Mayerhofer, Tim; Wood, Laurel; Osborn, John W.
Abstract: Hypertension is the leading modifiable risk factor for death worldwide, yet the causes remain unclear and treatment remains suboptimal. Catheter‐based renal denervation (RDNX) is a promising new treatment for resistant hypertension, but the mechanisms underlying its antihypertensive effect remain unclear. We recently found that RDNX attenuates deoxycorticosterone acetate‐salt hypertension and that this is dependent on ablation of afferent renal nerves and is associated with decreased renal inflammation. To determine if this is common to other models of salt‐sensitive hypertension, rats underwent complete RDNX ( n  =   8), selective ablation of afferent renal nerves ( n  =   8), or sham denervation ( n  =   8). Mean arterial pressure (MAP) and heart rate were measure by telemetry and rats were housed in metabolic cages for measurement of sodium and water balance. Rats were then subjected to angiotensin II (AngII)‐salt hypertension (10 ng/kg/min, intravenous + 4% NaCl diet) for 2 weeks. At the end of the study, renal T‐cell infiltration was quantified by flow cytometry. AngII resulted in an increase in MAP of ~50 mmHg in all three groups with no between group differences, and a transient bradycardia that was blunted by selective ablation of afferent renal nerves. Sodium and water balance were unaffected by AngII‐salt treatment and similar between groups. Lastly, AngII infusion was not associated with T‐cell infiltration into the kidneys, and T‐cell counts were unaffected by the denervation procedures. These results suggest that AngII‐salt hypertension in the rat is not associated with renal inflammation and that neither afferent nor efferent renal nerves contribute to this model. Abstract : Renal nerves are believed to contribute to the development of hypertension and this may be due to a novel interaction with renal inflammation. This study investigated the contribution of both efferent and afferent renal nerves to hypertension in rats treated with angiotensin II (AngII) and high sodium intake. Although previous findings have shown that renal nerve ablation is effective in some models of experimental hypertension, our findings indicated renal nerves do not contribute to AngII‐salt hypertension or renal inflammation in rats.